Kinesthetic differentiation, kinematic and dynamic parameters in sports climbing competitors of varying ability levels - Gasior, P. (Journal of Kinesiology and Exercise Sciences, 2020)
Aim of the study: To determine the differences in dynamic and kinematic parameters and kinesthetic differentiation of movement between competitors practicing sports climbing at different levels of advancement. Material and methods: The research group consisted of 30 men ( x _ = 25.6 years). The respondents were divided according to their level of experience (amateur, intermediate, advanced) into three groups of ten people. Measurements were taken of: relative strength, relative power and climbing speed for the upper and lower limbs using the Myotest accelerometer (Switzerland). To assess kinesthetic differentiation of movement, a two-plate stabilographic scale test (double-plate posturograph) was used. Results and conclusions: In climbers of greater ability we observed higher values for kinematic and dynamic parameters of the upper limbs. In the evaluation of the same parameters for the lower limbs we observed inverse relationships with climbing ability. Advanced climbers were characterized by lower relative power and relative strength of the lower limbs and also by a lower climbing speed. Compared with the amateurs, the advanced climbers who practice bouldering are characterized by a higher level of kinesthetic differentiation in posturographic tests for the shoulder girdle. The research results did not display any statistically significant differences in the level of abilities for kinesthetic differentiation of movement in measurements involving lower limbs. The research confirmed that dynamic and kinematic parameters of the upper limbs, including relative strength, relative power and climb speed, are significant determinants of the ability level of a boulderer. In the assessment of the lower limbs, these parameters do not influence ability level in bouldering. Thanks to the use of an innovative method of examining kinesthetic sensation, we noted that climbers of greater ability are more susceptible to the short-term effect of learning kinesthetic sensation when differentiating active strength (action) in the upper limbs. The double-plate posturograph is a tool which may be used for training and observing changes in terms of these coordination abilities. In response to the inclusion of climbing in the program for the Olympics as a three event competition, the introduction of training measures influencing relative power and strength parameters of the lower limbs should be considered. Optimizing training based on the development of relative power and speed of the lower limbs in competitors who practice bouldering may improve performance in speed climbing which, in the context of the multi-event competition, is of great importance.